Review jurnal: konsep teritorial arsitektur perilaku pada desain rest area - Afiyah, Rofifa Nur (Maliki Interdisciplinary Journal, 2025)
This journal, entitled “The Concept of Territorial Behavior Architecture in Rest Area Design,” discusses the application of the territorial concept in the design of a rest area located in Bojo, Mallusetasi District, Barru Regency. The purpose of the design is to provide comfort for drivers. This research was conducted to understand how behavioral architecture elements can be used effectively in rest area design, especially in the context of space division based on visitor characteristics. This is in accordance with the mandate of Law Number 22 of 2009. The research methods used by the author include data collection through field surveys and literature studies to understand the physical characteristics of the location and design requirements. The analysis was conducted using descriptive, synthetic, and exploratory methods. The results of the study show that the application of the territorial concept in rest and dining areas can increase visitor comfort by creating spatial boundaries that are in accordance with the characteristics and needs of users. This territorial concept consists of fixed, semi-fixed, and non-fixed elements, which function as regulators of space division based on user flexibility and interaction. Thus, this approach provides a design solution that is adaptive and responsive to user behavior in rest areas.